Distribution of electric field above a segment of a dielectric irradiated by an electron stream; Russian Physics Journal; Vol. 20, iss. 2 - Zavadovskaya E. K.; Zausaeva N. N.; Starodubtsev V. A. Viacheslav Alekseevich; Fedorov B. V. (1977, 1977)
Title screen